Second primary malignancies in head and neck region – a current problem in ENT oncological surgery - Wierzbicka, Małgorzata; Szyfter, Witold (Contemporary Oncology/Współczesna Onkologia, 2003)
On the basis of epidemiological data. In the last two decades the problem of second primary tumors (SPT) as a cause of failures in head and neck cancer treatment was widely discussed. On the basis of epidemiological data it was stated, that if the first tumor is localised in the upper part of the aerodigestive tract, the probability of second tumor development in this area increases significantly. The percentage of second primary tumors rising in the mucosa of the upper part of the aerodigestive tract is higher than any statistics of cancer incidence for chosen age groups and ranges from 9 to 35% according to different authors. More than a half of SPT is developing in two years’ time after the first tumor treatment. The adequate assessment of the metachronic SPT risk may be performed based on the number of new cases per year – for head and neck cancer it is between 1.5–10%. The survival rate rapidly decreases for the second tumors and ranges from 8 to 12%. The second tumor is the cause of death in more than 70% of cases while the first tumor in about 15%. In the ENT Dept. of Karol Marcinkowski University of Medical Sciences, 563 patients with head and neck cancer were treated in the period between January 2001–December 2002. In this group, 63 cases of SPT were found (10.5%), in out of which 40% were synchronic SPT and 60% – metachronic SPT. The primary localisation (index tumor) in which the probability of the second tumor development was higher was the oral cavity and the oral part of the pharynx (6 patients, i. e. 7.5% per year) and the larynx (26 patients, i. e. 6.5% per year). There were 56 men and 4 women. The factor of significant impact on the second tumor occurrence was the stage of the first tumor advancement (17 patients T1N0 and T2N0). It also correlates with higher grading of the histological examination. SPT was strictly connected with smoking and alcohol abuse (90% of patients). The meaningful factor was previous radiotherapy (50% of SPT). The majority of SPT cases were found when the patient complained about the neoplasm. The routine follow-up of patients and early detection of SPT is crucial for successful treatment.